PENGEMBANGAN MODEL PEMBELAJARAN PROJECT BASED LEARNING (PJBL) BERBANTUAN MEDIA INTERAKTIF UNTUK MENINGKATKAN LITERASI SAINS PESERTA DIDIK SEKOLAH DASAR - Setiani, Henny; Mariyam, Ima; Hoirunnisa, Siska; Sulastri, Syahwa; Ghifari, Agi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mastery of scientific literacy from elementary school is crucial for students to respond to the complexities of life in the global era. This study aims to develop and test the feasibility and effectiveness of a PjBL model integrated with interactive media as a strategic solution to improve science competency at the elementary school level. This study was designed using a Research and Development (R&D) framework that refers to the systematic procedures of the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. A total of 60 fifth-grade students from three public elementary schools in Serang City were selected as research participants through sampling. Data collection was carried out using expert validation instruments, student perception questionnaires, and scientific literacy test instruments developed based on the PISA 2022 framework. Quantitative analysis was applied using a paired-sample t-test and the calculation of the normalized N-Gain index. The feasibility assessment by expert validators resulted in an average percentage of 87.4% for the content aspect and 89.1% for the media aspect, both of which are classified as highly valid. Empirically, the model implementation showed a statistically significant difference (p < 0.05) with an N-Gain of 0.68, categorized as a moderate improvement. These results confirm that the synergy between the PjBL approach and interactive media effectively builds an inquiry-based learning ecosystem, which also accelerates scientific thinking skills, real-world problem solving, and active student participation in the science learning process.